Post a New Question

Math

posted by on .

Solve this substitution:
2x-5x=-8
-3x-2y=-26

  • Math - ,

    Did you mean 2x - 5y = -8 for the first one ?

    I will assume that is what you meant:

    Personally I would not use substitution, but ....

    from the 2nd
    26-3x = 2y
    (26-3x)/2 = y

    into the 1st:
    2x - 5(26-3x)/2 = -8
    times 2 to get rid of that fraction ...
    4x - 5(26-3x) = -16
    4x - 130 + 15x = -16
    19x = 114
    x = 6
    then y = (26-18)/2 = 4

    x = 6 , y = 4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question